Information Resources on Internet and Information Services in L&ICs - Das, Suchitra (Journal of Information and Knowledge, 2014)
Information is a resource for the management of an information system. The present paper discusses the information sources available on Internet and possible information services in Library and Information Centers. Talks about their availability on web site, guide to surf the available ocean of information resources, the information contents of the available resources; and their possible organisation and dissemination in L&ICs as a challenge for the library professionals. It also highlights the economics of periodicals subscription because of the arrival of scientific publishers on web site. Limitations to access the available sources on website are also discussed.